Let $f:X\to Y$ be a continuous map, and let $M_f = (X\times I) \sqcup Y)/(x,0)\sim f(x)$ be its mapping cylinder. Then the inclusion $X\to M_f$ is a cofibration.

My attempt:

Using the following theorem from Bredon seems like the most promising route:

1.5. Theorem. Assume that $A \subset X$ is closed and that there exist a neighbourhood $U$ of $A$ and a map $\phi : X \to I$, such that:

  1. $A = \phi ^{-1} (0)$;
  2. $\phi (X \setminus U) = \{ 1 \}$;
  3. $U$ deforms to $A$ through $X$ with $A$ fixed. That is, there is a map $H : U \times I \to X$ such that $H(a,t) = a \ \forall a \in A$, $H(u,0) = u$, and $H(u,1) \in A \ \forall u \in U$.

Then the inclusion $A \hookrightarrow X$ is a cofibration. The converse also holds.

Let us define a map $$\phi: M_f \to I, \quad (x,t)\mapsto \min(1,2-2t);\,\, y\mapsto 1$$ Then $\phi^{-1}(0) = X \times \{1\}$. Let $U$ be the upper half of the mapping cylinder. Then $\phi(U^c) = \{1\}$. Also, $X\times \{1\}$ is a strong deformation retract of $U$ I think.

So, by the theorem, the inclusion $X\to M_f$ is a cofibration.

I'm not sure if I'm on the right track. Is there a better way to do this? Is my way correct?

  • 1
    $\begingroup$ Thanks, can u help me understand why $X\times \{1\}$ is a strong deformation retract of $U$? It seems kinda obvious on the pictures I've been drawing, but I cant formulate a rigorous argument $\endgroup$ Mar 20 '15 at 15:22
  • 2
    $\begingroup$ Actually nevermind, the map $$H:U\times I \to U \\ ((x,s),t)\mapsto t(x,1) + (1-t)(x,s)$$ does the job $\endgroup$ Mar 20 '15 at 15:54
  • 2
    $\begingroup$ Hey, that's the same map as in my answer. Well, not a surprise, as it's the most obvious function :-) $\endgroup$ Mar 20 '15 at 15:59

As the OP was asking for it, here's a rigorous argument as to why $X\times\{1\}$ is a deformation retract of $U$.

The set $U$ is $X\times\left(\frac12,1\right]$, and its product topology makes it a subspace of $M_f$ since it is open and consists of entire equivalence classes. One possible map $U\times I\to M_f$ deforming $U$ onto $X\times\{1\}$ would be $$(x,s,t)\mapsto (x,t+(1-t)s)$$ as a map $U\times I\to X\times I\to M_f$ or, I you like, a map $U\times I\to U\hookrightarrow M_f$


I'm not sure if it couldn't be shortened. Please, correct me if I'm wrong. All we have to show is that this inclusion allows us to extend homotopies. Sorry, I don't know how to draw diagrams; it would be easier, but it's late now.

So we have homotopy $F: X \to P(Y)$ (the cocylinder to $Y$) and $i: X \to Z(X)$ (the cylinder of $X$) together with $f: Z(X) \to Y$ and $p: P(Y) \to Y$ and want to construct $F': Z(X) --> P(Y)$ in such a way that the appropriate diagram would be commutative. But this is easy (I suppose), because $i$ is a homotopy equivalence, so we can take its inverse $j$ and take $F'=Fj$ and it would be fine. Right?

Take care!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.